EYE-HAND COORDINATION, STATIC BALANCE WITH SHOOTING ACCURACY OF UKM PETANQUE UIR ATHLETES - Ramadhini, Dea; Apriani, Leni; Alpen, Joni (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The aim of this research is to investigate the relationship between the shooting accuracy of athletes from UIR Petanque UKM and their static balance and eye-hand coordination. This study falls under the category of multiple correlation research, and it involved 18 male participants from the UKM Petanque UIR. The instruments used for exploration included a dexterity test, static balance test, and petanque shooting test. The data analysis method employed was the multiple correlation value test. Based on the results of the research that has been done, the following conclusions can be drawn (1) There is a relationship between hand-eye coordination and the shooting accuracy of UIR petanque athletes with rcount = 0.581 > rtable = 0.468. (2) There is a relationship between static balance and the shooting accuracy of UIR petanque athletes with a value of rcount = 0.605 > rtable = 0.468. (3) There is a relationship between eye-hand coordination and static balance on the shooting accuracy of UIR petanque athletes with rcount = 0.697 > rtable = 0.468